2016
DOI: 10.1186/s10194-016-0651-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy and safety of Botulinum Toxin A Therapy in Trigeminal Neuralgia: a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundSeveral different interventions have been examined to alleviate pain and reduce frequency of trigeminal neuralgia (TN) paroxysms. However, some patients continue to have persistent or recurrent painful attacks. Using a systematic review and meta-analysis approach, we aimed to synthesize evidence from published randomized controlled trials (RCTs) regarding safety and efficacy of botulinum toxin type A (BTX-A) as a possible emerging choice of treatment for TN.MethodsWe conducted an electronic search in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 35 publications
3
76
0
7
Order By: Relevance
“…Recently, three reviews have demonstrated that BTX-A may provide a clinically significant benefit in treating TN (Morra et al, 2016), PN (Shackleton et al, 2016), and DNP (Lakhan et al, 2015). However, thus far, few investigations have explored the evidence for the overall effect of BTX-A on TN and PNP.…”
Section: As Early As 2002 Micheli Et Al Reported That a 70-year-oldmentioning
confidence: 99%
“…Recently, three reviews have demonstrated that BTX-A may provide a clinically significant benefit in treating TN (Morra et al, 2016), PN (Shackleton et al, 2016), and DNP (Lakhan et al, 2015). However, thus far, few investigations have explored the evidence for the overall effect of BTX-A on TN and PNP.…”
Section: As Early As 2002 Micheli Et Al Reported That a 70-year-oldmentioning
confidence: 99%
“…Muscle relaxants such as tizanidine and anti‐arrhythmics such as tocainide were studied as well. Chemodenervation with onabotulinumtoxinA has been found to be effective for treatment of trigeminal neuralgia; however, the techniques and dosing have often been different among the several studies done . Clinicians often use these same medications in painful trigeminal neuropathies from various causes, however there is very limited evidence for the use of oral pharmacologic therapy in these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The application of BTX-A to relieve TN was first reported in 2002, and its safety and effectiveness was later confirmed by series studies [3][4][5][6][7][8][9][10][11][12][13]. In 2012, our team conducted the first RCT study in this field, and obtained the prima facie evidence of BTX-A for TN.…”
Section: Commentarymentioning
confidence: 99%